The decline of life : old age in eighteenth-century England - Ottaway, Susannah R., 1967- (Cambridge studies in population, economy, and society in past time, 2004)
This is an important new study of the history of ageing. Ottaway combines a comprehensive survey of existing literature with original interpretation and analysis of available data, using a wide variety of sources. Her lively and sophisticated analysis will be of great interest to scholars in British and social history.